Passive noise control design for residential building near highways / Nafisah Mahussin - Mahussin, Nafisah (Faculty of Architecture, Planning and Surveying, 2015)
Noise is derived from the Latin word “nausea” implying ‘unwanted sound’ or ‘sound that is loud, unpleasant or unexpected’. The noise originates from human activities, especially the urbanization and the development of transport and industry. The passive method is a simple approach which includes the use of absorbers, barriers to reduce the interior noise in an enclosure. For enclosure structures on passive vibration noise control, the vibration and the noise are reduced either by adding appropriate passive elements or by modifying the system. It also can use the method to reduce noise such as acoustical site planning, architectural design, construction method and barrier construction. With use the soundproof window will reduce noise levels by 75-95%. More than 90% of all the exterior noise comes in through the door and window. Glass or Acrylic interior windows for maximum sound control, an 80% sound reduction and more can be had over the performance of the prime window. This research was conducted to investigate the method use to absorb noise in residential area1 building, to identify affect of sound pollution to the occupant, to identify the materials for noise control in residential building and to recommend the best method for noise control in residential area/ building. The opinion and views of related parties in the residential areas near highways were obtained from questionnaire and equipment in case studies which have been identified to give a clearer picture of the situation of the noise pollution and find the ways to reduce noise in residential building near highways